Role of native vesicular-arbuscular mycorrhizal fungi In wheat (Triticum aestivum) - based cropping sequence for efficient use of phosphorus and zinc in black soils of Madhya Pradesh - KHARE, A K; RAWAT, A K; DUBEY, S B; PATEL, K S; RATHORE, G S; THOMPSON, J P; TAKKAR, P N (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during 1989-92 to study the role of native vesicular-arbuscular mycorrhizal fungi in wheat (Triticum aestivum L. emend. Fiori & Paol.) in Zn-deficient black soil. The 2 cropping sequences, viz fallow-wheat (C1) and sorghum [Sorghum bicolor (L.) Moench]/soybean [Glycine max (L.) Merr.] - wheat (C2) in addition to 9 levels of zinc were used in 3 zinc deficient sites of Vertisol of Jabalpur and Narsinghpur districts of Madhya Pradesh. At Surai and Khamond the survival and multiplication of native vesicular-arbuscular mycorrhiza propagules in C2cropping sequence played a significant positive role over Cl cropping sequence in promoting the vesicular-arbuscularmycorrhiza colonization of roots, nutrient concentration, uptake and yield in wheat-based cropping sequence.